Stock lending and short-selling: evidence from national pension service in Korea - Lee, Kuan Hui; Wang, Shu Feng (Journal of Derivatives and Quantitative Studies, 2022)
The National Pension Service (NPS) of Korea suddenly announced that they would suspend their stock lending business from October 22, 2018. Using this ideal setting, the authors investigate the effects of this suspension on market quality and short-selling activities. The authors find that stock return does not increase after the suspension of stock lending for both the KOSPI and KOSDAQ markets. However, the returns of stocks with NPS ownership decline less than those without NPS ownership. The authors also find that the institutional and foreign investors' short sales did not increase in both markets after the lending business suspension by the NPS. In addition, the effect of suspension of stock lending on market quality is mixed, so the authors cannot conclude that market quality has improved. Overall, the authors’ results indicate that the stock market, especially for short-sales activity, has not been affected by the suspension of the stock lending service by the NPS.
Keywords: Korean stock market; National pension service (NPS); Short selling; Stock lending